Implementation of Self-Help Housing Stimulant Assistance (BSPS) Policy In Kauneran Village, Sonder District, Minahasa Regency - Tangkere, Stenly Imanuel; Tumbel, Goinpeace H.; Mamonto, Fitri H. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The research was conducted in North Sulawesi Province, focusing on Kauneran Village, Sonder District, Minahasa Regency. This location was chosen because initial data showed that the area was one of the major recipients of BSPS assistance.The purpose of this research is to Describe, analyze and explain the Implementation of the Self-Help Housing Stimulus Assistance (BSPS) Policy in Kauneran Village, Sonder District, Minahasa Regency,This study will use a qualitative approach with the aim of gaining an in-depth understanding of the implementation of the Self-Help Housing Stimulus Assistance policy, as well as identifying the determinant factors that influence the success and obstacles to program implementation in the field. Based on the results of research and discussions that have been conducted regarding the implementation of the Self-Help Housing Stimulus Assistance (BSPS) policy, several main points can be concluded as follows: The implementation of the BSPS Policy in Kauneran Village has not been fully optimal, although in general it is running according to procedure. Several indicators show success such as the distribution of building materials, community involvement, and the involvement of craftsmen. However, there are still technical and non-technical obstacles that hinder the effectiveness of the program.